Republic of Indonesia Financial Sector Assessment Program : Basel Core Principles Assessment - International Monetary Fund; World Bank (Washington, DC, 2017)
Indonesian financial sector comprises banks, multi-finance companies, capital market companies, insurance companies, and pension funds. The banking sector accounts for about 80 percent of the financial sector assets. It is dominated by 121 commercial banks, which account for about 98.6 percent of total banking assets (including 5 sharia banks accounting for 1.8 percent market share), with rural banks comprising the remainder of the banking system (about 1.4 percent market share). Bank Indonesia (BI), the central bank, is responsible for regulation and supervision of the banking system. The assessment of compliance with the Basel Core Principles for Effective Banking Supervision (BCP) was carried out within the framework of the Financial Sector Assessment Program (FSAP) between September 29 and October 16, 2009.